Surgical outcome and clinical profile of emergency versus elective cases of colorectal cancer in College of Medical Sciences, Nepal - Kumar, Sujit; Kafle, P; Patowary, BN; Belbase, N; Agrawal, S; Shrestha, S; Maharjan, N (Journal of College of Medical Sciences-Nepal, 2014)
Background: Patients who undergo emergency colorectal cancer surgery has poor outcome compared to elective surgery, both in terms of morbidity and mortality. Approximately 15 to 30% of colorectal cancers present as an emergency, most often as obstruction or perforation. Objective: To compare surgical outcome and clinical profiles of emergency and elective cases for colorectal cancer. Methods: Retrospective analysis of 34 cases who underwent surgery for colorectal cancer between December 2011 to January 2013was carried out and their surgical outcomes, clinical presentation, demographic profile were analyzed. Results: The total numbers of patients included in this study were 34. Out of which 52.94 %( n=18) were emergency cases and 47.05 %( n=16) were elective. Male female ratio was 3:1 in emergency cases and 2.6:1 in elective cases. Per rectal bleeding (56%) and altered bowel habit (31.25%) was predominant clinical presentation in elective cases whereas intestinal obstruction (55.55%) and peritonitis (22.22%) were predominant clinical presentation in emergency cases. In emergency cases most of the tumors were located in left side (77.77%) and in elective cases rectum was common site (37.5%). Left hemicolectomy was the commonest surgery performed (72.22%) in emergency set up. In elective cases, right hemicolectomy, left hemicolectomy, APR and LAR was done in 31.25%, 31.25%, 25% and 25% cases respectively. In the emergency group 11.11% (n=2) developed enterocutaneous fistula and early mortality within 30 days was observed in 5% (n=1) of emergency cases only. Conclusion: In emergency conditions, colorectal cancer presented with intestinal obstruction where as elective cases presented with per rectal bleeding and altered bowel habits. Compared with the elective patients, the emergency patients had higher rate of morbidity and mortality. Because of higher incidence of colorectal cancer in our institution, in all emergency cases who presents with features of intestinal obstruction and peritonitis, we have to rule out colorectal cancer especially if the patients are elderly. Therefore, we should encourage screening programme for early detection of colorectal cancers for better outcome of surgery. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 25-30 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9684